2021
DOI: 10.3390/antiox10020221
|View full text |Cite
|
Sign up to set email alerts
|

The Ameliorative Role of Acacia senegal Gum against the Oxidative Stress and Genotoxicity Induced by the Radiographic Contrast Medium (Ioxitalamate) in Albino Rats

Abstract: Arabic gum (Acacia senegal, AG) is proven effective antioxidant and cytoprotective agent. The present study was designed to test this notion by investigating the possible role of AG against the radiographic contrast medium (Ioxitalamate, Telebrix-35®, TBX)-induced oxidative stress and genotoxicity. Albino rats were divided into four groups and supplied with either; distilled water, daily 10% (w/v) AG, an intravenous dose of TBX (1600 mg I/kg b.wt) and co-administration of TBX and AG. Rats were sacrificed and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 94 publications
0
24
0
Order By: Relevance
“…Several reports have provided the information about the ethnopharmacological applications of foods and herbal medicines of indigenous to the arid regions of African countries and the Indian subcontinent [ 16 18 ]. Acacia senegal (L.) Willd.is typically known by its common name, white gum tree, and is a member of the Leguminosae-Mimosoideae [ 11 , 19 ], while seed extracts of Acacia senegal (L.) Willd.is locally known as kumbat or kumatiya in Rajasthan [ 20 , 21 ]. The present study also identified the major phytoconstituents present in the seed extracts of Acacia senegal and assess its anti-atherosclerotic properties in hypercholesterolemic rabbits using a combination of in-vitro , in-silico , and in-vivo methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have provided the information about the ethnopharmacological applications of foods and herbal medicines of indigenous to the arid regions of African countries and the Indian subcontinent [ 16 18 ]. Acacia senegal (L.) Willd.is typically known by its common name, white gum tree, and is a member of the Leguminosae-Mimosoideae [ 11 , 19 ], while seed extracts of Acacia senegal (L.) Willd.is locally known as kumbat or kumatiya in Rajasthan [ 20 , 21 ]. The present study also identified the major phytoconstituents present in the seed extracts of Acacia senegal and assess its anti-atherosclerotic properties in hypercholesterolemic rabbits using a combination of in-vitro , in-silico , and in-vivo methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been carried out and showed that these gums were not genotoxic. 30 El-Garawani et al (2021) 31 suggested that Arabic gum exerted a protective role against TBX-induced oxidative stress and genotoxicity which may be attributed to its active metabolites. Primary scientific study done by Qureshi et al (1993), 32 aimed to assess cytotoxic and genotoxic effects of myrrha gum using normal and Ehrlich ascites carcinoma cell-bearing Swiss albino mice; results indicated that it had a significant cytotoxic potential and no genotoxic effect.…”
Section: Genotoxicity Assessementmentioning
confidence: 99%
“…However, the observed mass spectra consider the fingerprint of these compound that can be identified from the data library. It was widely reported that Arabic gum contained a considerable number of phytochemicals that exhibit antioxidant activity and can combat many diseases such as renal, cardiovascular, gastrointestinal, and respiratory diseases, due to its agonist effect on the oxidative stress and DNA damage [92]. Furthermore, Badreldin et al verified the antioxidative and anti-inflammatory properties of AG.…”
Section: Chemical Profile Of Ethanol Asg Extract Using Gc-tofmsmentioning
confidence: 99%